2008
DOI: 10.1021/jf801458d
|View full text |Cite
|
Sign up to set email alerts
|

Toward Better Understanding of Salt-Induced Hen Egg White Protein Aggregation Using Field-Flow Fractionation

Abstract: Field-flow fractionation techniques including sedimentation field-flow fractionation (SdFFF) and flow field-flow fractionation (FlFFF) were applied to investigate hen egg white protein aggregation. The thermally induced aggregation of hen egg white protein was observed at temperatures of 60 degrees C and higher. Particle size and size distribution of hen egg white protein aggregates were characterized by SdFFF to investigate parameters affecting ZnCl 2-induced aggregation of hen egg white protein. At a fixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In both cases the proteins remained negatively charged and aggregates were not formed. The results agreed with those obtained by Samontha et al [74].…”
Section: Proteinssupporting
confidence: 93%
See 1 more Smart Citation
“…In both cases the proteins remained negatively charged and aggregates were not formed. The results agreed with those obtained by Samontha et al [74].…”
Section: Proteinssupporting
confidence: 93%
“…The combination of several analytical techniques collectively allowed a reliable assessment of protein self-association and aggregation phenomena. Samontha et al [74] used AsFlFFF and sedimentation FFF (SdFFF) under such conditions that led to hen egg white protein aggregation. At pH > 5 with protein concentration of 2%, and ∼25 mM ZnCl 2 , AsFlFFF and SdFFF could be efficiently utilized to control the aggregate size of hen egg white protein.…”
Section: Proteinsmentioning
confidence: 99%
“…To perform salt-induced gelation of proteins, CaCl 2 and ZnCl 2 were used as they are listed as generally recognized as safe (GRAS) by the United States of America Food and Drug Administration when used in accordance with good manufacturing practice (FDA, 2008). Our earlier investigations indicated that salt-induced gelation of BLG or HEW was best achieved by CaCl 2 or ZnCl 2 , respectively (Saeseaw et al, 2006;Samontha, Nipattamanon, Shiowatana, & Siripinyanond, 2008). One might argue that aggregate formation could already be obtained by mixing BLG with a-TOC.…”
Section: Resultsmentioning
confidence: 97%
“…Hen egg white aggregation induced by ZnCl 2 and/or pH has been studied by a combination of symmetrical FlFFF and sedimentation FFF (SdFFF) (Samontha, Nipattamanon, Shiowatana, & Siripinyanond, 2008). SdFFF was utilized to study the formation of aggregates and FlFFF to investigate the amount of proteins that remain non-aggregated.…”
Section: Other Food Proteinsmentioning
confidence: 99%